Speech Act of Commissives and Expressives: A Case Study on the Speech of Tun Dr. Mahathir in the 1MDB issue (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
This study deals with the speech act of commissives and expressive in the speech of Tun Dr. Mahathir during the year of 2015 until 2017. Ten of Dr. Mahathir’s speeches was selected for analysis using the theoretical framework introduced by Searle (1969, 1979). The selection of data was conducted base on the purposive sampling, namely choosing a speech that focused on one issue - 1Malaysia Malaysian Development Berhad (1MDB). Generally, speech act of commissives is utterances binds the speaker to what is spoken. Speech act of expression is utterances that expresses the feeling and emotions of the speaker. In term of the speech act of commissive, this study found Tun Dr. Mahathir only made his promise after he established the Parti Peribumi Bersatu Malaysia and when he started campaigning for the 14th General Election (GE14). Among the promises that he made are to save the country from kleptokrasi leaders, restore justice, scholarship, do no practice corruption and so on. In term of speech act of expressive, the analysis found 16 subcategories. Out of these number, a total of 13 related expressive on the 1MDB issue. Among subcategories of speech act of expressive are acts of desire, confidence, worry, shame, and so on. His desire in the speech is to find out the truth behind 1MDB. This study concludes that the speech act of commissive is only delivered when he left UMNO and started campaigning for GE14 as a solution to the 1MDB problem. In addition, the act of expression also shows Tun Dr. Mahathir is trying to get a detailed explanation of 1MDB.
Keywords: Speech Act; commissive, expression, Tun Dr. Mahathir, 1MDB.